Key issues in the teaching of Spanish pronunciation from description to pedagogy - Rao, Rajiv 1979- (Routledge advances in Spanish language teaching, 2019)
Key Issues in the Teaching of Spanish Pronunciation: From Description to Pedagogy is a resource that encourages Spanish teachers and curriculum designers to increase their incorporation of pronunciation into the classroom. Combining theory and practical guidance, it will help language practitioners integrate the teaching of Spanish pronunciation with confidence and effectiveness. The international group of scholars across its 15 chapters is made up of individuals with well-established research records and training in best pedagogical practices. Key features: A range of topics including vowels, various classes of consonants, prosody, the use of technology, the role of orthography, the importance of both perception and production, individual learner differences, and teacher training; Overviews of descriptive, empirical, and acquisition-based research associated with each aspect of the Spanish sound system; Guidance on the difficulties that teachers face when incorporating the teaching of pronunciation into the classroom; Clear explanations of concepts, accompanied by an abundance of concrete examples and references; Multiple sample activities and lesson plans tailored to different levels and backgrounds of students; A bilingual glossary of terms to help the content reach the widest audience possible. Written in a clear and accessible manner, Key Issues in the Teaching of Spanish Pronunciation is an essential resource for teachers of Spanish at all levels. It is also an excellent reference book for researchers and both undergraduate and graduate university students interested in Spanish phonetics and language acquisition